MAIN FEATURES OF PRESENTING SOCIAL LIFE DESCRIPTION IN ENGLISH CLASSES (ON THE MATERIAL OF SHORT STORIES) - Seytniyazova , Guljakhan Mirzagalievna; Aytbaeva, Makhinur Axmed qizi (Educational Research in Universal Sciences, 2023)
This article is devoted to the study of the main features of the presentation of the description of social life in English in the classroom. The authors use story analysis to describe various aspects of life in an English-speaking society and consider ways to include this topic in the learning process. The article also contains recommendations and examples of exercises that will help students better understand and remember information about life in English-speaking countries.